2020
DOI: 10.1093/asj/sjaa238
|View full text |Cite
|
Sign up to set email alerts
|

Facelift Surgery Turns Back the Clock: Artificial Intelligence and Patient Satisfaction Quantitate Value of Procedure Type and Specific Techniques

Abstract: Background Patients desire facelifting procedures to look younger, refreshed, and attractive. Unfortunately, there are few objective studies assessing the success of types of facelift procedures and ancillary techniques. Objectives The authors sought to utilize convolutional neural network algorithms alongside patient-reported FACE-Q outcomes to evaluate perceived age reduction and patient satisfaction following various facel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…10 Further, there was no difference on satisfaction scores between facelift techniques which correlates with other studies in the literature. 5,10 This level II study provides strong evidence for patient satisfaction, 10 yet additional studies with patient-reported outcomes are needed.…”
Section: Surgical Treatmentssupporting
confidence: 86%
See 1 more Smart Citation
“…10 Further, there was no difference on satisfaction scores between facelift techniques which correlates with other studies in the literature. 5,10 This level II study provides strong evidence for patient satisfaction, 10 yet additional studies with patient-reported outcomes are needed.…”
Section: Surgical Treatmentssupporting
confidence: 86%
“…Patients utilizing a variety of facelift techniques were compared using FACE-Q scores and 77% of patients reported high levels of satisfaction and 85% of patients reported high satisfaction with their decision to have the procedure. 10 Further, there was no difference on satisfaction scores between facelift techniques which correlates with other studies in the literature. 5,10 This level II study provides strong evidence for patient satisfaction, 10 yet additional studies with patient-reported outcomes are needed.…”
Section: Surgical Treatmentssupporting
confidence: 86%
“…13 While studies have suggested that skin tone does not appear to influence the outcome of such computer analysis, 27 given the discordance with physician clinical assessments as shown in this study, perhaps, it is time to consider alternatives such as artificial intelligence, 28 patient-reported outcomes (e.g. FACE-Q surveys), 28 and even eye tracking technology 29 for more objective and valid (i.e. by the patients) assessments.…”
Section: Discussionmentioning
confidence: 84%
“…Vectra) and showed that there was a statistically significant ( p = .033) reduction in jawline volume between the injected half-face with XEO when compared with the other half with normal saline as control 12 and that such an effect persisted for up to 3 months. 13 While studies have suggested that skin tone does not appear to influence the outcome of such computer analysis, 27 given the discordance with physician clinical assessments as shown in this study, perhaps, it is time to consider alternatives such as artificial intelligence, 28 patient-reported outcomes (e.g. FACE-Q surveys), 28 and even eye tracking technology 29 for more objective and valid (i.e.…”
Section: Discussionmentioning
confidence: 86%
“…The FACE-Q adds a valuable perspective on the effectiveness of facelift procedures alongside traditional outcome measures such as morbidity and may provide the means to incorporate patient perspective and individualize our daily practice's algorithmic approach. For example, one study showed their artificial intelligence model to correctly estimate patients’ age reduction after different facelift techniques [ 60 ].…”
Section: Discussionmentioning
confidence: 99%